Contemporary diasporic literature - Manjit Inder Singh (Pencraft International, 2007)
Transcript of papers presented at a seminar organized by the Dept. of English, Punjabi U., Patiala on February 24-25, 2005 Proceedings of the National Seminar: Contemporary Diasporic Literature : Writing History, Culture, Self , held at Patiala during 24-25 February 2005
Includes passages in Panjabi
Keywords: Konferenzschrift; Indic literature (English); East Indians; East Indian diaspora in literature; Indic literature; Culture in literature; History in literature